2011
DOI: 10.1159/000328802
|View full text |Cite
|
Sign up to set email alerts
|

A Case of High-Grade Neuroendocrine Carcinoma That Improved with Bevacizumab plus Modified FOLFOX6 as the Fourth-Line Chemotherapy

Abstract: High-grade neuroendocrine carcinoma differs from usual neuroendocrine carcinoma, and its prognosis is dismal. In this case report, a case of high-grade neuroendocrine carcinoma that improved with bevacizumab plus modified FOLFOX6 as the fourth-line chemotherapy is presented. A 29-year-old male with a huge liver tumor was diagnosed with high-grade neuroendocrine carcinoma originating from the liver. Multiple liver and bone metastases were found one month after surgery. He was treated with three chemotherapy reg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 10 publications
(8 reference statements)
0
3
0
Order By: Relevance
“…EP regimen may have been considered as one of the best choice for NEC so far, but unfortunately, the insurance system in Japan did not cover the regimen for NEC. Although modified FOLFOX6 plus bevacizumab was not commonly used for MANEC, some studies have reported administration of FOLFOX regimen to patients with MANEC and its effectiveness [12,13]. Additionally, at least 30% of the MANEC tumor comprises adenocarcinoma.…”
Section: Discussionmentioning
confidence: 99%
“…EP regimen may have been considered as one of the best choice for NEC so far, but unfortunately, the insurance system in Japan did not cover the regimen for NEC. Although modified FOLFOX6 plus bevacizumab was not commonly used for MANEC, some studies have reported administration of FOLFOX regimen to patients with MANEC and its effectiveness [12,13]. Additionally, at least 30% of the MANEC tumor comprises adenocarcinoma.…”
Section: Discussionmentioning
confidence: 99%
“…There are reports of clinical benefit when combined with existing chemotherapy treatments [148, 149]. …”
Section: Systemic Therapiesmentioning
confidence: 99%
“…Vascular endothelial growth factor (VEGF) is overexpressed in NETs and targeted by the ligand monoclonal antibody Bevacizumab [ 40 , 146 , 147 ]. There are reports of clinical benefit when combined with existing chemotherapy treatments [ 148 , 149 ].…”
Section: Systemic Therapiesmentioning
confidence: 99%